Estudo da concentração de vapor d’água na camada limite atmosférica sobre a região da confluência Brasil-Malvinas - Freitas, Rose Ane Pereira de (2017)
The atmosphere is the smallest contributor of the planet's water tanks providing only 0.001% of the water total mass. However, it is of fundamental importance for playing a key role in the atmosphere's physical processes. The concentration of water vapor on the marine atmospheric boundary layer (MABL) at the Brazil-Malvinas Confluence (BMC) region in the Southwestern Atlantic Ocean was analyzed from ralative humidity profiles from 130 radiosondes taken in situ from ships. These data were collected during 10 oceanographic cruises carried out during the months of October or November from 2004 to 2015. During the same period, specific humidity and air temperature data from reanalysis (CFSR/CFSv2) and from the Atmospheric Infrared Sounder (AIRS) onboard the Aqua satellite were also used. From this data, the sea surface temperature (SST) gradients and the passage of atmospheric synoptic scale transient systems over the BMC region were evaluated aiming to determine its relation with the spatial and temporal variability of water vapor concentrations inside the MABL in the region. Previous works prove that the BMC region, known for its intense SST horizontal gradients, is responsible for the MABL's local modulation and the maintenance of intense lateral gradients of latent and sensible heat fluxes between the atmosphere and the ocean. The results of this work show that the thermal gradients between the warm waters of the Brazil Current (BC) and the cold waters of the Malvinas Current (MC) in CBM region are capable to produce significant differences on the MABL's water vapor content on both sides of the oceanographic front. On the average over the warmer waters of the BC the MABL is more humid, with a mean precipitable water near 2 kg.m- 2 higher than in the cold waters, MC dominated region. This work shows that, as reported in previous works in the same region, that the MABL is locally modulated by the SST. However, transients atmospheric systems, common in this region of the planet, can mitigate or intensify the concentration of water vapor inside the MABL, as well as to cause temperature advection. The comparison between in situ radiosonde data and AIRS and CFSR profiles revealed that, in general, the CFSR/CFSv2 data presented a better agreement with observational data in both sides of the BMC. The AIRS data satisfactorily represent the observational data in conditions of a cloud-free atmosphere. Nevertheless, they also depend on the time difference between the times of acquisition of both observational and satellite data. The different advection conditions of the atmosphere are also important. The greatest differences between the observed and satellite profiles of specific humidity and air temperature were found at the top of the MABL and at levels were inversions of these variables were present.